The networks of care surrounding cancer palliative care patients. Issue 4 (26th March 2015) - Jarrett, N; Porter, K; Davis, C; Addington-Hall, J; Duke, S; Corner, J; Lathlean, J
Abstract : Objectives: This paper explicates the nature and extent of the networks of care surrounding patients with cancer palliative care needs. Method: Twenty-four patients with 15 different types/sites of cancer were recruited in one city in England, UK. During one in-depth interview patients identified who was 'involved in their care' and any known pathways of communication between them. One hundred of these people (35 doctors, 32 nurses, 17 professions allied to medicine, 8 family members and 8 others) were also interviewed. Maps of people/teams and the connections between them for each patient were then reconstructed using social networking software (PAJEK). Results: The 24 patients identified a total of 619 people or teams (mean 26, median 22, range 9–45 per patient) contributing to their care. Selected care network maps are displayed, illustrating the extent and nature of the care networks supporting palliative care patients. Common members of care networks for patients with palliative care needs are revealed, but their individual and unique nature is also apparent. Conclusions: The possible clinical utility and challenges of mapping care networks are discussed. Exploring the care networks surrounding individual patients can be useful for illuminating the extent and complexity of individual patient's care networks; clarifying who is involved and who they communicate with; providing opportunities to see interaction routes that may otherwise be hidden, revealing potentially missing or weak connections; and highlighting overlaps or gaps in provision.